Alkali Metal Ions Induced Electrochemical Oscillations in H2O2 - H2SO4 - Pt System. (10th December 2015) - Mukouyama, Yoshiharu; Kawasaki, Hirokazu; Hara, Daisuke; Kikuchi, Mitsunobu; Yamada, Yuri; Nakanishi, Shuji
Abstract : A new electrochemical oscillation, named oscillations J, has been found to appear during the H2 O2 reduction on Pt in strongly acidic solutions. It appears both as current and potential oscillations when the salts such as Na2 SO4 and K2 SO4 are added to the acidic solutions containing H2 O2 . The appearance of oscillation J is attributed to the presence of alkali metal ions such as Na + and K + ions, which increases the local pH at the electrode surface from acidic to basic during H2 O2 reduction. Furthermore, oscillation J also appears during H2 O2 reduction in strongly basic solutions. Although the role of an N-shaped negative differential resistance (N-NDR) for oscillation J is not clarified yet, oscillation J is probably classified into a coupled N-NDR (CN-NDR) oscillator.